Sosialisasi Peraturan Daerah Sumatera Utara Nomor 1 Tahun 2019 Tentang Fasilitasi Pencegahan Penyalahgunaan Narkotika, Psikotropika, Dan Zat Adiktif Lainnya - Shulhan Iqbal Nasution; Nanang Tomi Sitorus; Dhea Aulia Malem Purba; Qori Rizkiqiah H Kalingga; Alvin Hamzah Nasution (Civiliza Publishing, 2026)
The abuse of narcotics, psychotropics, and other addictive substances (NAPZA) is still a serious problem because it causes various negative impacts on social life, health, and the quality of human resources, especially among the younger generation. As a preventive measure, the North Sumatra Provincial Government stipulated Regional Regulation Number 1 of 2019 concerning the Facilitation of the Prevention of Abuse of Narcotics, Psychotropics, and Other Addictive Substances. This article aims to examine the role of socialization of regional regulations in increasing the effectiveness of preventing narcotics abuse in the community. The research uses normative legal methods with a legislative approach and a conceptual approach through the study of various legal sources and related literature. The results of the study show that socialization activities contribute significantly to increasing public legal understanding and awareness, strengthening public involvement, and building cooperation between local governments, educational institutions, the media, the business sector, and the community. Therefore, socialization that is carried out continuously is an important factor in supporting the successful implementation of regional regulations and creating an environment free from narcotics abuse.